Assessing the workforce adaptive capacity of seaports to climate change: an Australian perspective. Issue 7 (2nd October 2020) - Chhetri, Prem; Gekara, Victor; Scott, Helen; Thai, Vinh V.
ABSTRACT: This paper explores the adaptive capacity of the Australian port workforce and its preparedness to manage the likely impact of climatic shifts and extreme weather events. Qualitative interviews and focus groups were conducted across three case-ports in which a wide range of adaptive capacity elements, including systems and processes, skills and knowledge and organizational culture and norms, were explored. In total, 15 interviews and three focus groups were organized, totaling 69 participant-hours of rich qualitative data. Findings suggest that the ports seem to have established a variety of systems and processes to cope with and manage the impacts of extreme weather events. Although acknowledging the need for continuous improvement, the management staff were confident about the effectiveness of current systems and processes to tackle the potential threats from extreme weather events. The general view was that additional adaption measures are not required to specifically deal with the impacts of extreme weather. However, it was also acknowledged that strengthening of adaptive capacity could be enhanced by mainstreaming climate considerations into existing risk evaluation, workforce management, and operational systems. Whilst sustainability issues are becoming increasingly important to port businesses, it is argued that ports should integrate climate change adaptation as part of their wider risk management strategies, as well as their sustainable development agenda to update and guide the actions, behaviours, and practices of the port workforce.